# Elementary logic: ...therefore, ~(B ▼ P) → ~(A ▼ E

#### Mariellow

##### New member
 1. A → (B ▼ C) 2. E → (C ▼ P) 3. ~C /∴ ~(B ▼ P) → ~(A ▼ E
Can somebody help me with the elementary logic, please. I need to prove the validity of the argument. Thank you!

#### mmm4444bot

##### Super Moderator
Staff member

Read the forum's submission guidelines, also. Thank you!

#### Mariellow

##### New member
I have tried direct and indirect proof.

#### Dr.Peterson

##### Elite Member
You'll need to be much more specific. SHOW YOUR EFFORTS, not just a vague description. Maybe you were almost right, and we'd never know without seeing it!

#### pka

##### Elite Member
 1. A → (B ▼ C) 2. E → (C ▼ P) 3. ~C /∴ ~(B ▼ P) → ~(A ▼ E
Can somebody help me with the elementary logic, please. I need to prove the validity of the argument. Thank you!
I have worked on all things in symbolic logic since 1962 but I have never seen the connective ▼.

#### Mariellow

##### New member
A-> (BvC)
E -> (CvP)
~C therefore ~(BvP)->~(AvE)
Here it is sir. Sorry for the wrong symbol

#### Mariellow

##### New member
I don't know whats the next step to do. Sorry

#### Attachments

• 3.3 MB Views: 3